Quelle écologisation de la pratique des paysagistes concepteurs ? - Brice Dacheux-Auzière; Yves Petit-Berghem (Projets de Paysage)
The article seeks to identify the temporal and spatial references indicating changes in the way ecological requirements are taken into account in the practice of landscape architecture regarding the notion of biodiversity. The archives of the last 27 years (1988-2015) of the review Paysage Actualités were scanned. A simple quantitative lexicometric process was applied based on key words such as “biodiversity” and “tree”. Qualitative data contained in the articles (texts and graphic documents) were then analysed making it possible to identify the emergence of an ecologization of the profession and the factors behind it.